A ἄσκησις de desapropriação epictetiana à luz da Κάθαρσις do Fédon de Platão - Rodrigues, Antonio Carlos de Oliveira (2015)
The katharsis concept exposed in Plato s Fédon was absorbed and incorporated to Epictetus desire exercise. As katharsis was moved from its place of origin to Epictetus s spiritual exercise, it suffered transformations to adapt to the zenonian rule of life conduct. Epictetus strongly believes that to live in conformity with nature one needs to put a lot of effort towards the separation of body and soul. So that, to him, only the men who possesses freedom acquires, at the same time, the ability to accept life as it is, becoming capacitated to receive with complete indifference whatever may destiny bring. To Epictetus the abolition of all soul s enslavement starts with the separation of ours and someone else s and completes itself with the comprehension that someone else s is nothing to us